Pengaruh Persepsi Dukungan Organisasi dan Budaya Organisasi terhadap Kinerja Karyawan - Hariani, Mila; Irfan, Mochamad (TIN: Terapan Informatika Nusantara, 2024)
This study aims to analyze the effect of Perceived Organizational Support (POS) and Organizational Culture on Employee Performance in the manufacturing sector of Mojokerto City. Perceived Organizational Support reflects the extent to which employees feel valued and supported by the organization, while Organizational Culture includes values, norms, and beliefs that shape employee behavior in the workplace. This study used an explanatory quantitative approach involving 100 employees from various levels of positions. The results showed that POS and Organizational Culture have a significant influence on employee performance, both individually and together. POS encourages employee loyalty and motivation by increasing their sense of security and job satisfaction. A positive Organizational Culture encourages cooperation, innovation, and adaptation to change, which contributes to increased productivity and work efficiency. This research underscores the importance of creating synergy between POS and Organizational Culture to create a work environment conducive to individual and organizational growth. The practical implications of this research are the importance of reward policies, recognition of employee contributions, and the development of a collaborative work culture. The results of this study provide strategic insights for manufacturing companies to improve human resource management to support organizational success.